Assessment and management of mucositis in head and neck cancer patients. (December 2012) - Bonomi, Marcelo; Camille, Nadia; Misiukiewicz, Krzysztof; Latif, Asma; Gupta, Vishal; Blacksburg, Seth; Genden, Eric; Posner, Marshall
Oral mucositis (OM) is a significant problem in patients with head and neck cancer undergoing chemoradiation treatments. Severe OM develops in more than 90% of patients undergoing combined chemotherapy and radiation. OM is not only painful but also limits adequate nutritional intake and decreases the patient's willingness to continue treatment. When severe, it is responsible for acute and chronic complications such as aspiration, prolonged dysphagia, scarring and fibrosis. In spite of all the advances made in understanding the pathobiology of OM, there is currently no prophylactic therapy with proven efficacy. Strategies to limit the extent of OM and to manage its symptoms include basic oral care, supportive medications, nutritional support and limiting the use of aggressive treatments to high-risk patients. This review focuses on OM recognition, preventive measurements, symptom-management strategies, and identifies current research studies addressing OM prevention.